Penggunaan media pembelajaran berdasarkan gaya belajar siswa slow learner di Kelas V SD Negeri 53 Banda Aceh - Nurdin, Miftahul Jannah; Israwati, Israwati; Mislinawati, Mislinawati (Universitas Syiah Kuala, 2023)
The purpose of this research is to explain how slow students in fifth grade at SD Negeri 53 Banda Aceh may make use of effective learning material that is tailored to their individual learning styles. This study employs a qualitative, descriptive methodology. Slow learners at the Vc level were the focus of this research; the sample included 4 students (2 male and 2 female). Observation and in-depth interviews are used for data collecting. The analysis phase involves the processing of all data obtained so far, including data reduction, data display, and the development of conclusions based on the data. Learning media and the learning styles of slow learners have a positive impact on the learning process, according to the findings of studies on the topic. Using learning material that is suited for slow learner pupils would make the teaching process simpler for the instructor, as data analysis shows that there are outcomes for each learning type among slow learners.